Factors Affecting the Blood Level of Phenytoin in Thai Children with Epilepsy: A retrospective study: Pawalee Niamtaworn - Kangwantas, Korakoch; Phodha, Tuangrat; Niamtaworn, Pawalee (Princess of Naradhiwas University Journal, 2024)
Phenytoin is a medication for epilepsy with a narrow therapeutic index. There is not nearly as much at the therapeutic level in children. Therefore, it is very crucial to study the factors affecting the blood level of phenytoin. This study aimed to study factors affecting the blood level of phenytoin in Thai children with epilepsy, aged 1 month to 18 years, who were hospitalized to tertiary hospitals between 2014 and 2018. The cross-sectional study was used to gather electronic data. Data analysis utilized in this study was Multivariate logistic regression. The results found that phenytoin was administered to 275 subjects. A blood level of phenytoin test was administered 107 times to the 59 subjects. The blood level of phenytoin was statistically substantially correlated with gender, age group, comorbidities, and highly protein bound drugs (p<0.05). Phenytoin levels in the blood were associated with male gender, infant group, comorbidities, and highly protein bound drugs. In contrast to the teenage group, the toddler group had a factor associated with the blood level of phenytoin. In conclusion, age group, comorbidities, and highly protein bound drugs should be taken into consideration when administrating phenytoin. These factors affect the blood level of phenytoin, which can become ineffective in controlling epileptic symptoms and medicine safety.